Transformasi Cara Penuturan Cerita dalam Bentuk Aplikasi Digital Storytelling sebagai Media Pengenalan Kembali Legenda â€œCalon Arangâ€ - M.P., Denny; Mutiaz, Intan Rizky; Sriwarno, Andar Bagus (Nirmana, 2013)
The legend of Calon Arang is one of many legends known by the Indonesian people. This legend can be said as a unique one, considering that this widely known dramatari (a mix between drama and tari = dance) Legenda Calon Arang is only performed in Bali, but actually the legend itself came from Kediri, East Java. Nevertheless, in today's society, this tradition is starting to be left behind. Calon Arang is only held on special occasions and considered to be sacred, which means this performance can't be held at any moment. The threat also comes from foreign culture such as popular culture, that usually together with the offers of new mass production technology products, causes more and more people to easily accept foreign cultures, but slowly neglecting and leaving behind their original tradition. This research is conducted as a further step to bring back the legend of Calon Arang, as one of Indonesianâ€™s heritage, using new media which is digital media in the form of digital application. Based on theories of the visual storytelling theory, digital storytelling, and also visual language/Wimba that are presented in the form of digital application, a media that is widely known by today's society, the expectation is to make modern society know and enjoy the story, and also its philosophical values.